Circadian immune system in solid organ transplantation: a review article - Yim, Wai Yen; Li, Chenghao; Tong, Fuqiang; Hou, Jincheng; Chen, Yuqi; Liu, Zongtao; Wang, Zihao; Geng, Bingchuan; Wang, Yixuan; Dong, Nianguo (Frontiers in Immunology, 2025)
The innate and adaptive immune systems are intricately regulated by the circadian clock machinery. Recent clinical investigations have shed light on the influence of timing in organ procurement and transplantation on graft survival. In this review, we explore various mechanisms of immunological functions associated with the steps involved in organ transplantation, spanning from surgical harvesting to reperfusion and linking to the circadian rhythm. A deeper understanding of these processes has the potential to extend the principles of chrono-immunotherapy to the realm of organ transplantation, with the aim of enhancing graft durability and improving patient outcomes. This review concludes with some perspectives on future directions in this exciting and still evolving field of research.